Skrining Fitokimia dan Uji Aktivitas Antioksidan dengan Metode DPPH Ekstrak Benalu Pohon Mahoni (Loranthus sweietenia macrophylla) - Oktaviani, Mila (Journal of Pharmacy Tiara Bunda, 2023)
Mahogany tree (Swietienia macrophylla king) has many benefits as an antioxidant, starting from the roots, bark, leaves, even the mistletoe that lives on this plant. Mahogany mistletoe leaves (Loranthus swietenia macrophylla) were used as samples in this study to test their antioxidant activity. This study was conducted because many have conducted antioxidant tests on mistletoe leaves such as mengkudu mistletoe leaves, coffee mistletoe leaves, mango mistletoe leaves and kersen mistletoe leaves. Mahogany mistletoe leaves (Loranthus swietenia macrophylla) were used as samples in this study to test their antioxidant activity. Before the antioxidant activity test was carried out, a phytochemical screening test was first carried out as a qualitative analysis stage to determine the secondary metabolite content in mahogany mistletoe leaves. Mahogany mistletoe leaves were dried in variations of 0 days (S), 4 days (KA4), and 8 days (KA8) which were extracted by maceration with 96% ethanol solvent. The results of the phytochemical screening test showed that mahogany mistletoe leaf extract contains secondary metabolite compounds such as flavonoids, phenolics, alkaloids, saponins, terpenoids, and steroids. The total phenolic content was 25.25; 48.29; and 52.82 mgGEA/g extract for extracts S, KA4, and KA8, respectively. Furthermore, the antioxidant activity test using vitamin C as a comparator with the DPPH (2,2-Diphenyl-1-picrylhydrazyl) method showed IC50 values ​​of 10.79; 8.00; 7.41 ppm for extracts S, KA4, and KA8, respectively, indicating that the highest antioxidant activity was possessed by sample KA 8 with an IC50 value of 7.41 ppm with a total phenolic content of 52.82 mgGEA/g